The examination of small-scale magnetic-field structures in the solar wind using two spacecraft - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2025)
To explore some properties of small-scale magnetic structures in the solar wind at 1 AU, measurements from the THEMIS-ARTEMIS mission with two spacecraft in orbit around the Earth’s moon are used. The small-scale magnetic structures are categorized into four types: discontinuities (current sheets), magnetic flux tubes (including twisted flux tubes), magnetic holes, and small-amplitude magnetic-field fluctuations. The large-scale solar-wind structures in which the small-scale structures are investigated are noted. The two-spacecraft measurements are used to examined differences in the structures over spatial scales of a few RE. Further, a two-spacecraft methodology was used to examine the planarity of discontinuities over scales of a few Earth radii.